Metal-free oxidation of secondary benzylic alcohols using aqueous TBHP. Issue 21 (1st November 2016) - Wu, Jianglong; Liu, Yan; Ma, Xiaowei; Liu, Ping; Gu, Chengzhi; Dai, Bin
ABSTRACT: We report a simple, yet efficient metal-free oxidation of secondary benzylic alcohols in the presence of t-butyl hydroperoxide (70% TBHP) with high yields of up to 98%. This type of reaction can be carried out using a wide variety of substrates, requires no other organic solvent, and proves to be tolerant toward a variety of different functional groups. GRAPHICAL ABSTRACT: